Expression of Senescence-Associated Secretory Phenotype in Senescent Gingival Fibroblasts - Sangim Lee (The Korean Society of Dental Hygiene Science, 2023)
Background: Although microbial infection is direct cause of periodontal disease, various environmental factors influence the disease severity. Aging is considered a risk factor for oral diseases, with the prevalence of periodontal diseases increasing with age. Moreover, senescence-associated secretory phenotype (SASP) expressed in age-related diseases is a key marker of chronic inflammation and aging phenotypes. Therefore, this study aimed to understand the relevance of senescent cells to periodontal health and disease, investigate the possibility of regulating the expression of aging- and osteolysis-related factors in gingival fibroblasts, and investigate the effect of senescence induction in gingival fibroblasts on osteoclast differentiation in mouse bone marrow-derived macrophages (BMMs). Methods: After stimulation with 400 nM hydrogen peroxidase, human gingival fibroblasts (HGFs) were examined for senescenceassociated ‐galactosidase. Western blot and enzyme-linked immunosorbent assays were performed to assess the expression of SASP. Osteoclast formation was assessed in BMMs using a conditioned medium (CM) from hydrogen peroxide-stimulated HGFs. Osteoclastic differentiation was investigated using tartrate-resistant acid phosphatase (TRAP) staining and activity. Data analysis was performed using SPSS version 25.0. Results: The expression of senescence-related molecules, including p53, p16, and p21, and the expression of osteolytic factors, including IL-6, IL-8, and IL-17, were found to be significantly higher in the hydrogen peroxide-stimulated HGF than in the control group. Regarding the indirect effects of senescent gingival cells, the number of osteoclasts and TRAP activity increased according to the differentiation of BMM cultured in CM. Conclusion: Our results on the of between osteolytic factors and cellular senescence in gingival fibroblast cells helped to reveal evidence of pathological aging mechanisms. Furthermore, our results suggest that the development of novel therapies that target specific SASP factors could be an effective treatment strategy for periodontal disease.